Organic pollutant removal from edible oil process wastewater using electrocoagulation - Sharma, Swati; Can, Orhan Taner; Hammed, Monsur; Nawarathna, Dharmakeerthi; Simsek, Halis (Iop Publishing Ltd, 2018)
Wastewaters generated from vegetable oil industries contain a high concentration of organic pollutants that are detrimental to the aquatic ecosystem. Electrochemical processes are gaining importance in the treatment of inorganic and resistant organic pollutants in wastewaters. In this study, electrocoagulation (EC) was applied to remove organic pollutants and oil and grease from canola oil wastewater using aluminum (Al) and iron (Fe) electrodes. The application of EC in the wastewater achieved more than 80% removal of organic carbon and nearly 100% removal of suspended solids (SS). The effectiveness of EC is influenced mainly by current density, pH, electrolyte (NaCl), electrode contact time and electrode type. It was observed that Al electrode combination yielded better removal at a lesser time compared to that of Fe electrodes. However, varying current densities had its significance in terms of coagulation time only. Increase in current density achieved decrease in coagulation time. Both Al and Fe could remove between 52-59% of oil and grease from canola oil wastewater
4th International Conference on Sustainable Agriculture and Environment (ICSAE) -- AUG 10-12, 2017 -- Surakarta, INDONESIA
CAN, Orhan Taner/0000-0003-3386-975X
Keywords: [No Keywords]